Serotonin Levels in the Serum of Persons with Onchocerciasis-Associated Epilepsy: A Case-Control Study - Vieri, Melissa Krizia (Pathogens, 2021)
Onchocerciasis-associated epilepsy (OAE) is a devastating childhood disorder occurring in areas with high Onchocerca volvulus transmission. Despite epidemiological evidence showing the association between O. volvulus and epilepsy, the underlying mechanism remains unknown. Since high levels of serotonin are known to induce seizures, we investigated serotonin levels in persons with OAE and controls selected from the Democratic Republic of Congo. Serum serotonin levels were determined by ELISA in 19 persons with OAE, 32 persons with epilepsy without O. volvulus infection, 18 with O. volvulus infection but without epilepsy, and 35 with neither O. volvulus infection nor epilepsy. O. volvulus infection was diagnosed by skin snip testing and/or OV16 antibody detection. Serum serotonin levels were significantly decreased in persons with OAE compared to persons with O. volvulus infection and no epilepsy. In conclusion, an increased serotonin level is unable to explain the pathogenesis of OAE. Other hypotheses to identify the causal mechanism of OAE will need to be investigated.